ANALISIS PERILAKU KONSUMEN KARTU GSM TELEPON SELULAR PADA PT. TELKOMSEL DI MALANG SEBAGAI DASAR PENETAPAN STRATEGI PERUSAHAAN - Triatmanto, Boge (Fakultas Ekonomi, UIN Maliki Malang, 2009)
This research observes the consumer behavior toward the usage of GSM card for cellular phone on PT. Telkomsel. Objectives of the research are to find out the consumer interest in using the GSM card on PT. Telkomsel and to find out the proper strategy which will be applied by PT Telkomsel in order to expand its market. The Observation is conducted on three areas: condition of the GSM-premiere card user, satisfaction level of the consumer and loyalty level of the consumer to the company products. This research uses internal and external environmental analysis that applying PLC, SWOT, and BCG analysis techniques. The research recommends that the company should, first, consider the internal as well as external factors which influence the consumer behavior in using the products of PT. Telkomsel Malang. Second, the company should determine the variation strategy in order to achieve optimal level of the consumer satisfaction. Third, it should determine a generic strategy, expansion, in order to achieve a well-known company of GSM card in Malang.